Clinical evaluation of posterior flowable short fiber-reinforced composite restorations without proximal surface coverage - Abd ElAziz, Rawda H. (Springer Nature, 2025)
The purpose of this clinical trail was to assess the clinical behavior of posterior composite restorations supported by a substantial foundation of flowable short fiber-reinforced composite SFRC (everX Flow, GC, Japan) used without proximal surface coverage with particulate filler resin composite (PFC). Seventy patients (20 males, 50 females; mean age: 30 ± 10 years) were randomly enrolled in this trial. Patients received direct restorations of either SFRC covered only on the occlusal surface (1-2 mm) by conventional PFC composite (G-ænial Posterior, GC), or plain conventional PFC composite without fiber-reinforcement, in Class II cavities in premolar and molar vital teeth. One operator made all restorations using one-step, self-etch bonding agent (G-ænial Bond, GC) according to manufacturers' recommendations. Two blinded trained operators evaluated the restorations at baseline, at 6, 12 and 18 months using modified USPHS criteria. Results indicated that, in both groups and at different follow-up intervals, according to evaluated criteria, restorations were rated mostly with best score (Alpha) (p > 0.05). For the marginal integrity after 6 months, a single case in the intervention [increased to 3 (8.8%) after 18 months] and 3 (9.7%) cases of the control group [increased to 4 (12.9%) after 18 months] had Bravo score but with no significant difference (p > 0.05). For color match measured after 6 and 18 months, three (8.8%) cases had Bravo score in the intervention group. The use of flowable SFRC composite without any PFC surface coverage proximally in Class II restorations demonstrated satisfactory clinical outcome throughout the 18-month follow-up.